The Epic of Gilgamesh - McCaughrean, Geraldine; Parkins, David (Grand Rapids, Mich. : Eerdmans Books for Young Readers, 2003)
A retelling, based on seventh-century B.C. Assyrian clay tablets, of the wanderings and adventures of the god king, Gilgamesh, who ruled in ancient Mesopotamia (now Iraq) in about 2700 B.C., and of his faithful companion, Enkidu.
9 and up.
Keywords: Gilgamesh -- Adaptations; Gilgamesh; Folklore -- Iraq